2012
DOI: 10.3892/mmr.2012.1070
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-regulated protein 75 overexpression attenuates ionizing radiation-mediated injury in PC12 cells by inducing the expression of topoisomerase IIα

Abstract: Abstract. Glucose-regulated protein 75 (Grp75), also known as mortalin/mthsp70/PBP74, is a member of the heat-shock protein 70 (HSP70) family. Grp75 is known to protect cells from stress-induced injury. Previous studies have shown that the expression of Grp75 is upregulated by a low dose of ionizing radiation (IR). To evaluate the protective role of Grp75 on cell proliferation in response to IR, Grp75 was overexpressed in a rat adrenal pheochromocytoma cell line (PC12). It was revealed that Grp75 overexpressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…In previous studies, GRP75 overexpression was associated with protection against cell death in cancer cells exposed to lethal cellular stress such as UV irradiation or in cultured astrocytes exposed to oxygen-glucose deprivation. 49 , 50 Here, we showed that GRP75 was involved in pro-death rather than pro-survival signaling in neuronal HT22 cells. We found that glutamate-induced cell death was prevented in GRP75 knockdown and KO cells, whereas GRP75 overexpression enhanced the sensitivity of neuronal cells to the oxidative insult.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…In previous studies, GRP75 overexpression was associated with protection against cell death in cancer cells exposed to lethal cellular stress such as UV irradiation or in cultured astrocytes exposed to oxygen-glucose deprivation. 49 , 50 Here, we showed that GRP75 was involved in pro-death rather than pro-survival signaling in neuronal HT22 cells. We found that glutamate-induced cell death was prevented in GRP75 knockdown and KO cells, whereas GRP75 overexpression enhanced the sensitivity of neuronal cells to the oxidative insult.…”
Section: Discussionmentioning
confidence: 75%
“…The discrepancy between our findings and the aforementioned studies might be attributed to the various cellular functions of GRP75 which seem to be different in different cell types. Besides its role in ER–mitochondrial coupling, GRP75 is also a major component of the mitochondrial import machinery, being identified as a regulator of MAPK (Akt/Erk)-dependent pro-survival signaling, 49 , 52 and being linked to the regulation of p53. Moreover, the cell death or disease model seems to influence the outcome of GRP75 modulation.…”
Section: Discussionmentioning
confidence: 99%
“…Interaction between GRP75 and IP3R1 has been demonstrated to increase upon axonal injury, contributing to increased ER-mitochondrial tethering, elevated mitochondrial Ca 2+ , and enhanced ATP generation to promote axonal regrowth (Lee et al, 2019). GRP75 overexpression is also associated with protection against cell death after exposure to cellular stress such as radiation and in astrocytes exposed to oxygen-glucose deprivation (Guo et al, 2012;Voloboueva et al, 2008). Overexpression studies also give rise to both mitochondrial stress response and protection against stress-induced ROS formation and loss of mitochondrial membrane potential in different cell types (Jin et al, 2006;Burbulla et al, 2014).…”
Section: Mitochondrial Function Is Defective In Glucose-deprived Atm-deficient Cells In Response To Nutrient Stressmentioning
confidence: 99%
“…GRP75 is a chaperone interacting with other proteins to regulate mitochondrial protein import, and to activate pro-survival signaling pathways through MAPK activation or pro-apoptotic p53-dependent signaling cascades 8 , 9 . In hepatocellular carcinoma cells, GRP75 inhibition substantially enhanced cell death which was linked to an increase in the nucleo-cytoplasmic shuttling of the tumor suppressor p53, thereby driving apoptosis 10 .…”
mentioning
confidence: 99%